Digitalisasi Informasi dan Keberlimpahan Berita di Era Pascakebenaran - Mudjiyanto, Bambang; Launa, Launa; Yanuar, Fit (FISIP Universitas Bung Karno, 2024)
Information credibility in the era of digital society as an impact of the abundance of information is no longer a logical and ethical measure in the media sphere. Information truth and news accuracy are now only seen as a matter of public literacy, sharing errors, the negative impact of social media or legal problems; not a matter of fact integrity, news accuracy, and information ethics. This qualitative study with descriptive-interpretive analysis method characterized by virtual ethnography sees the erosion of logos and ethics as the cause of the digital society's easy exposure to the post-truth virus. Logos is the realm of facts, logic, truth, and valid reasoning. In the post-truth era, truth evaluation is postponed if not avoided; and lies have convincingly successfully masqueraded as valid arguments. In the post-truth era, truth and falsehood no longer have clear boundaries. Post-truth rhetoric and political agendas are certainly not only facilitated by social media, but by the reality where lies can wear the mask of truth. The multiplication of media and the spread of information sources in cyberspace are two crucial points that are most responsible for the growth of lies in the post-truth era.Keyword: Digital society, abudance of information, post-truth era, disinformed society